Comparative Study of Infiltration in Soils under Forest Cover and Agriculture in Temperate Climate - Mathur, R. N.; Singh, R. P.; Gupta, M. K. (Indian Forester, 1982)
Under both the condition of this study, the forest land has higher initial infiltration rates of 46.8 cm/hr and 5 cm/hr and final infiltration rates of .1 cm/hr in 150 mts and .1 cm/hr in 120 mts from forest areas as compared to .1 cm/hr in 60 mts ond 0 cm/hr in 20 mts from agricultural land after snow removal and snow melt respectively, due to thick layer of humus(10 cm) beneath the forest cover; higher organic matter (7.27%), higher moisture equivalent (29.87%), higher pore space (61.60%) and hIgher water balding capacity (60.26%) forest soils hafe resulted in higher infiltration rates in comparison to the agritultural soils, with no humus, low organic matter content (2.68%), lower moistnre equivalent (29.8%), lesser pore space (56.6%) and lower water holding capacity (46.88%).